2019
DOI: 10.3847/1538-4357/ab3e4b
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Observations of GRB 180720B: from Radio to Sub-TeV Gamma-Rays

Abstract: Early and late multiwavelength observations play an important role in determining the nature of the progenitor, circumburst medium, physical processes and emitting regions associated to the spectral and temporal features of bursts. GRB 180720B is a long and powerful burst detected by a large number of observatories in multiwavelenths that range from radio bands to sub-TeV gamma-rays. The simultaneous multiwavelength observations were presented over multiple periods of time beginning just after the trigger time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…The value of the initial bulk Lorentz factor inferred during the deceleration phase is similar to those reported by other burst detected by Fermi-LAT (Veres & Mészáros 2012). Since GRB 160509A exhibited one of the most energetic photons reported by Fermi-LAT in the second GRB catalog, it is expected that the value of the bulk Lorentz factor lies in the range of the brightest LAT-detected bursts (500Γ1000; Abdo et al 2009a;Ackermann 2010;Ackermann et al 2011;Ackermann 2013;Ackermann et al 2014;Fraija et al 2019bFraija et al , 2019c, as found in this work.…”
Section: The Bulk Lorentz Factorssupporting
confidence: 88%
“…The value of the initial bulk Lorentz factor inferred during the deceleration phase is similar to those reported by other burst detected by Fermi-LAT (Veres & Mészáros 2012). Since GRB 160509A exhibited one of the most energetic photons reported by Fermi-LAT in the second GRB catalog, it is expected that the value of the bulk Lorentz factor lies in the range of the brightest LAT-detected bursts (500Γ1000; Abdo et al 2009a;Ackermann 2010;Ackermann et al 2011;Ackermann 2013;Ackermann et al 2014;Fraija et al 2019bFraija et al , 2019c, as found in this work.…”
Section: The Bulk Lorentz Factorssupporting
confidence: 88%
“…The BAT light curve exhibited a multi-peaked structure with a duration of T 90 = 150 s [50]. Promptly, GRB 180720B was followed up by X-ray Telescope (XRT) and the Ultra-Violet/Optical Telescope (UVOT), by Fermi GMB and LAT [52,53], by Konus-Wind [54], by CALET Gamma-ray Monitor [55] and several orbiting and ground instruments in optical and radio bands [56]. The host galaxy of GRB 180720B was located to have a redshift of z = 0.654 [57].…”
Section: Grb 180720bmentioning
confidence: 99%
“…; Abdalla et al 2019) telescopes from high-luminosity bursts GRB 180720B and GRB 190114C, respectively. The high-energy and VHE photons detected by the Fermi Large Area Telescope (LAT), H.E.S.S., and MAGIC beyond the synchrotron limit were interpreted in the SSC forward-shock (FS) scenario (Fraija et al 2019c(Fraija et al , 2019aZhang 2019). On the other hand, llGRBs, characterized by being less energetic and having opening angles 30°, are not natural candidates to emit VHE photons.…”
Section: Introductionmentioning
confidence: 99%